2019
DOI: 10.1212/nxi.0000000000000538
|View full text |Cite
|
Sign up to set email alerts
|

Anti-MOG encephalitis mimicking small vessel CNS vasculitis

Abstract: ObjectiveTo report 2 patients with anti–myelin oligodendrocyte glycoprotein (MOG)-associated encephalitis who were initially misdiagnosed with small vessel primary CNS vasculitis.MethodsReview of symptoms, MRI and neuropathologic features, and response to treatment. MOG antibodies were determined in serum and CSF using a cell-based assay.ResultsSymptoms included fever, headache, and progressive mental status changes and focal neurologic deficits. CSF studies revealed lymphocytic pleocytosis, and both patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
53
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 6 publications
1
53
0
1
Order By: Relevance
“…44 Children with MOG antibodies are also less likely to have oligoclonal bands than those with MS. 42,44 However, the spectrum of brain disease associated with MOG antibodies in adults and children has broadened to include ADEM, meningoencephalitis, cortical encephalitis with seizures, brainstem encephalitis, and mimics of vasculitis. [45][46][47] Some of these patients will evolve into more typical demyelinating phenotypes, such as ADEM; therefore, MOG antibodies should be considered in pediatric AE presentations beyond ADEM. [45][46][47] MOG autoantibodies are typically transient in monophasic ADEM, but remain positive in relapsing phenotypes.…”
Section: Approach To Clinically Recognizable Syndromesmentioning
confidence: 99%
See 1 more Smart Citation
“…44 Children with MOG antibodies are also less likely to have oligoclonal bands than those with MS. 42,44 However, the spectrum of brain disease associated with MOG antibodies in adults and children has broadened to include ADEM, meningoencephalitis, cortical encephalitis with seizures, brainstem encephalitis, and mimics of vasculitis. [45][46][47] Some of these patients will evolve into more typical demyelinating phenotypes, such as ADEM; therefore, MOG antibodies should be considered in pediatric AE presentations beyond ADEM. [45][46][47] MOG autoantibodies are typically transient in monophasic ADEM, but remain positive in relapsing phenotypes.…”
Section: Approach To Clinically Recognizable Syndromesmentioning
confidence: 99%
“…[45][46][47] Some of these patients will evolve into more typical demyelinating phenotypes, such as ADEM; therefore, MOG antibodies should be considered in pediatric AE presentations beyond ADEM. [45][46][47] MOG autoantibodies are typically transient in monophasic ADEM, but remain positive in relapsing phenotypes. 8,9,42 Limbic encephalitis The clinical, EEG, and radiologic features of limbic encephalitis are uncommon in children.…”
Section: Approach To Clinically Recognizable Syndromesmentioning
confidence: 99%
“…All three cases underwent brain biopsy, which showed small vessel perivascular inflammation, consistent with CNS vasculitis. However, fibrinoid necrosis, a pathologic requirement for small vessel CNS vasculitis, was absent in two of the cases (66,67). Whether vasculitis should be regarded as a primary or secondary manifestation of MOGAD, or MOG-Ab is unrelated to vasculitis diagnosis, is difficult to determine given rarity of the association.…”
Section: Acute Disseminated Encephalomyelitis (Adem) and Other Cerebrmentioning
confidence: 97%
“…Finally, mention should be made of rare cases when MOG-Ab was found in patients with pathologically-proven CNS vasculitis ( 65 , 66 ). Two patients presented with fever, headache, confusion, and focal neurologic deficits ( 66 ), and the third had 9 months of progressive cognitive and behavioral decline ( 65 ). MRI showed multifocal lesions in both the gray and white matter in two cases, one of whom also had open-ring contrast-enhancing lesions.…”
Section: Acute Disseminated Encephalomyelitis (Adem) and Other Cerebrmentioning
confidence: 99%
“…In the March issue of N2, 2 groups described cases of patients with additional clinical conditions associated with MOG antibodies. 77,78 In 1 study, Patterson et al 77 reported on 2 patients exhibiting signs of small vessel CNS vasculitis. Both patients presented with fever, headaches, and mental status changes, and 1 had cranial nerve palsies.…”
mentioning
confidence: 99%